Proceedings of the 33rd Chinese Control Conference 2014
DOI: 10.1109/chicc.2014.6895705
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical fuzzy control of multivariable systems via semi-tensor product method

Abstract: A new kind of scheme is proposed to obtain hierarchical fuzzy control of multivariable systems. It is based on algebraic fuzzy reasoning equations of fuzzy system using semi-tensor product framework recently described. First, the bi-decomposition of multivariable fuzzy systems is considered, and some new results are obtained. Using these results, the algorithm of hierarchical fuzzy systems realization is developed such that one can easily design the middle layers of the hierarchical structure. The resulting hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The proposed fuzzy system is multivariable, and both the antecedent and consequent have several components. Although there are several strategies to build this type of system [37], [59], [60]. The rules were created according to the effect (Table IV) of each input variable on water stress; the building elements of the center pivot were also considered.…”
Section: G Rule Basementioning
confidence: 99%
“…The proposed fuzzy system is multivariable, and both the antecedent and consequent have several components. Although there are several strategies to build this type of system [37], [59], [60]. The rules were created according to the effect (Table IV) of each input variable on water stress; the building elements of the center pivot were also considered.…”
Section: G Rule Basementioning
confidence: 99%
“…Hedysarum Multijugum Maxim.-Chuanxiong Rhizoma Compound (HCC) was first used by the First Affiliated Hospital of Hunan University of Chinese Medicine. Clinical research showed that HCC has definite curative effect on cerebral ischemic diseases (such as ischemic stroke and CIR), and its clinical effective rate is over 90% (Ge, 2014). This Chinese medicine formula is composed of Hedysarum Multijugum Maxim.…”
Section: Introductionmentioning
confidence: 99%